2020
DOI: 10.1111/tme.12753
|View full text |Cite
|
Sign up to set email alerts
|

Motivators of and barriers to becoming a COVID‐19 convalescent plasma donor: A survey study

Abstract: Objectives To determine the motivators and barriers to COVID‐19 convalescent plasma donation by those in the United Kingdom who have been diagnosed with or who have had symptoms of SARS‐CoV‐2 (COVID‐19) but who have not donated. Background Convalescent plasma from people recovered from COVID‐19 with sufficient antibody titres is a potential option for the treatment and prevention of COVID‐19. However, to date, recruiting and retaining COVID‐19 convalescent plasma donors has been challenging. Understanding why … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(33 citation statements)
references
References 47 publications
2
31
0
Order By: Relevance
“…The awareness about CCP donation was higher in the state of Goa (96.4%)as compared to findings of Masser et al who reported that only 34.3% had heard of CCP. 21 In spite of having such high level of awareness, the percentage of COVID-19 plasma donors was very less (4.5%), Masser et al found that only one study participant had donated plasma. 21 Among those who had not donated plasma, the willingness to donate plasma was 49.1%, which is lower than reported by Dhiman et al (72.8%).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The awareness about CCP donation was higher in the state of Goa (96.4%)as compared to findings of Masser et al who reported that only 34.3% had heard of CCP. 21 In spite of having such high level of awareness, the percentage of COVID-19 plasma donors was very less (4.5%), Masser et al found that only one study participant had donated plasma. 21 Among those who had not donated plasma, the willingness to donate plasma was 49.1%, which is lower than reported by Dhiman et al (72.8%).…”
Section: Discussionmentioning
confidence: 99%
“…21 In spite of having such high level of awareness, the percentage of COVID-19 plasma donors was very less (4.5%), Masser et al found that only one study participant had donated plasma. 21 Among those who had not donated plasma, the willingness to donate plasma was 49.1%, which is lower than reported by Dhiman et al (72.8%). 22 Around 10.5% of the study population thought that they were ineligible for CCP donation, which is consistent with the findings of Masser et al who found that 9.9% of the study participants believed that they were ineligible for CCP donation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The convalescent plasma from recovered individuals with sufficient antibody titers has been attracted attention as a therapeutic option (68). There are many ongoing clinical trials in this regard; for example, RESCUE is an ongoing clinical trial to evaluate convalescent plasma's efficacy and safety in treating old-aged adults with SARS-CoV-2.…”
Section: Convalescent Plasmamentioning
confidence: 99%